Dramatic decreases of all haemorrhagic coagulation factors by acquired inhibitors after extended left lobectomy. (2019) - Sakuraoka, Yuhki; Suzuki, Takashi; Mtsumoto, Takatsugu; Tanaka, Genki; Shimizu, Takayuki; Shiraki, Takayuki; Kyongha, Park; Mori, Shozo; Iso, Yukihiro; Kato, Masato; Aoki, Taku; Kubota, Keiichi
Highlights: Required inhibitors of all coagulation factors. After liver resection. Severe bleeding. Benefits of using steroid. Abstract: Introduction: Acquired inhibition of coagulation factors is a rare disease, and the diagnosis is often difficult and delayed. We experienced a deficiency in all coagulation factors after hepatobiliary surgery. Case Presentation: Extended left liver resection was undertaken and hepaticojejunostomy was performed in a 70-year-old man. He had suffered from a high fever caused by cholangitis for 35 days. The major cause was a narrowing of the hepaticojejunostomy, and reconstruction was carried out. Twenty-four days later, there was a sudden massive bleed from his nose and the surgical site. Steroid pulse therapy was used as a treatment because cross mixing and some blood tests revealed the patient was experiencing an inhibition of all coagulation factors, and consequently the levels of coagulation factors dramatically recovered. Discussion: We considered malignancy and surgical damages to be the underlying cause. The reported treatment and examination will help clinicians explore additional reasons for massive bleeding after a severe physical injury. Conclusion: We have described the first case of acquired inhibition of all coagulation factors associated with extended left lobectomy.